2020
DOI: 10.17159/wsa/2020.v46.i1.7893
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the fate of natural organic matter at a drinking water treatment plant in South Africa using optical spectroscopy and chemometric analysis

Abstract: The removal dynamics of biodegradable dissolved organic carbon (BDOC) and natural organic matter (NOM) polarity fractions at a water treatment plant (WTP) in South Africa was studied using UV-Vis absorbance, fluorescence excitation-emission matrix, and two-dimensional synchronous fluorescence spectroscopy (SFS). This study gave insights into the transformation of NOM due to treatment processes. The objectives of the study were: (i) to use chemometric analysis and two-dimensional SFS correlations to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…These results suggest that tyrosine-, tryptophan-and fulvic-like matter were transformed or degraded concurrently throughout the treatment process. Our previous study found tyrosine to be more susceptible to treatment than the other fractions (Moyo et al 2020). This suggests NOM characteristics, treatment regimen and chemicals used play a role in the ease of removal of NOM fractions.…”
Section: Selective Elimination Of Chromophoric Dissolved Organic Matter Fractionsmentioning
confidence: 93%
“…These results suggest that tyrosine-, tryptophan-and fulvic-like matter were transformed or degraded concurrently throughout the treatment process. Our previous study found tyrosine to be more susceptible to treatment than the other fractions (Moyo et al 2020). This suggests NOM characteristics, treatment regimen and chemicals used play a role in the ease of removal of NOM fractions.…”
Section: Selective Elimination Of Chromophoric Dissolved Organic Matter Fractionsmentioning
confidence: 93%
“…Dissolved organic carbon was determined in the filtered samples using a total organic carbon analyzer (Teledyne Tekmar, TOC fusion). The method for the determination of BDOC is reported elsewhere (Moyo et al, 2020). Briefly, washed sand (100 g) was placed in 500-ml Erlenmeyer flasks covered with aluminium foil, and the water sample (300 ml) was added.…”
Section: Dissolved Organic Carbon Biodegradable Dissolved Organic Camentioning
confidence: 99%
“…and attributed it to the accumulation of dead microbes in the sand of the DAFF filters (Moyo et al, 2020). However, further research is needed to conclusively explain this phenomenon.…”
Section: Research Articlementioning
confidence: 99%
“…Optical methods provide advantages such as rapid detection, simple operation, and non-destructive sample analysis [7]. In recent years, with the advancement of new technologies such as optical and spectroscopic techniques, notably the emergence of three-dimensional fluorescence spectroscopy and UV-Vis absorption spectroscopy, rapid real-time monitoring of wastewater treatment plants has been rendered feasible [8][9].…”
Section: Introductionmentioning
confidence: 99%